Gender-specific impact of cadmium exposure on bone metabolism in older people living in a cadmium-polluted area in Thailand - Muneko Nishijo (2018)
© 2017 by the authors; licensee MDPI, Basel, Switzerland. To elucidate the influence of cadmium exposure on bone metabolism, associations between urinary/blood cadmium and bone resorption/formation markers were investigated in older cadmium exposed men and women. Increased urinary cross-linked N-telopeptide of type I collagen (NTx), a bone resorption marker, was found to be associated with increased levels of parathyroid hormone, fractional excretion of calcium, and urinary/blood cadmium after adjusting for confounding factors in men. In women, urinary NTx was significantly associated with only urinary cadmium and a strong relationship with increased fractional excretion of calcium. Risk for bone metabolic disorders, indicated by high urinary NTx, significantly increased in men with blood cadmium ≥ 10 μg/L or urinary cadmium ≥ 10 μg/g creatinine. Increased osteocalcin level was significantly associated with increased blood cadmium in men. In conclusion, cadmium exposure appeared to have an influence on bone remodeling both bone resorption and formation in this population of older Thai men, and blood cadmium was more closely associated with bone metabolism than urinary cadmium.